Anthony Caro : at Cliveden - Caro, Anthony, 1924-2013; Renshaw, Amanda; Fletcher, Jess (2019)
Featuring essays by curator and publisher, Amanda Renshaw charting the British sculptor?s career of ?restless investigation and rule breaking?; and by National Trust curator, Oonagh Kennedy providing a reflection on Caro?s work on site at Cliveden.00Also included are archive photographs of Caro and his work, complemented by stunning full-colour photography of each of the sculptures in situ. Sixteen monumental works by Caro are displayed across the Grade I listed grounds at Cliveden, charting Caro?s career and his distinctive approach to sculpture.00Installed along the Green Drive, the ensemble of sculptures, including Scorched Flats (1974) and Slow March (1985), accompany visitors on their journey, offering them an opportunity to contemplate the works and their relationship to the surrounding landscape.00Exhibition: The National Trust's Cliveden, Taplow, UK (06.04.? 10.11.2019).
Foreword / Graham Southern -- Anthony Caro's sculptures take the air at Cliveden / Amanda Renshaw.
Published on the occasion of the exhibition held April 6-November 10, 2019.
Includes bibliographical references.
Keywords: Caro, Anthony, -- 1924-2013 -- Exhibitions; Outdoor sculpture -- Exhibitions